(untitled) (Bangladesh Journal of Zoology, 2023)
Butterflies are widely regarded as the most reliable bioindicators of a healthy terrestrial ecosystem. This insect belongs to the order Lepidoptera of the class Insecta and plays an important role in preserving ecological dynamics. The objective of this paper is to review the species diversity of butterflies in Bangladesh. The data is based mainly on published records and field sampling. IUCN Bangladesh (2015) evaluated the threat status of 305 species of butterflies in 2015. The overall number of butterfly species in Bangladesh is now 421, with another 116 having just been added to the IUCN-Bangladesh list. Lycaenidae has the most species (124), followed by Hesperiidae (87), Nymphalidae (79), Satyridae (35), Pieridae (36), Papilionidae (32), Danaidae (19), Riodinidae (4), Amathusiidae (4), and finally Acraeidae, which has only one species. In the present review, it is shown that the family Lycaenidae has the highest percentage of butterfly species (29.45%) among the ten families. The number of Lycaenid butterflies is influenced by various factors, one of which is their ability to inhabit a diverse array of habitats. In contrast, Danaidae account for only 4.51% species of butterflies in Bangladesh, where only one Critically Endangered (CR) and endemic taxon, Euploea crameri nicevillei (Sundarban Crow) resides. Larval host plant documentation in the Sundarbans is essential for the conservation of this species, while the molecular data (COI gene) has already been sequenced and submitted to Genbank (MH269417). Finally, the data obtained from this paper is important for future planning and management of the conservation of the butterflies and their habitat in Bangladesh. Bangladesh J. Zool. 51(1): 03-34, 2023